A Late Military Use of the Sphero-conical in the 19th Century Sudan. (1st February 2017) - Pradines, Stéphane
Abstract : This paper focuses on a particular type of mace that was used by the Sudanese dervishes during the Mahdist rebellion from 1881 to 1899. These maces were a reuse of Mamluk sphero-conical vessels. They were associated with the standards (alams) of the Mahdist regiments. The association suggests these maces had some talismanic value to the dervishes. The author will examine their origin and propose a new interpretation of the sphero-conical vessels as objects linked to the Indian Ocean's Spice and Perfume trade.